NATIONAL AND INTERNATIONAL DEVELOPMENTS ON COPYRIGHT AND RIGHTS IN DATABASES - Khong, W. K. (Malaysian Journal of Library and Information Science, 2001)
Reports on recent changes to the Malaysian Copyright Act in relation to the protection of databases. Also, the development of the law in the European Union and the United States are examined. This article is an expanded version of a paper originally presented at the International Conference and Workshop on Multimedia Digital Library: Global Access & National Identity, 16–18 August 1999, Kuala Lumpur.